2005
DOI: 10.1021/bi0503448
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Cofactor Biosynthesis in Humans:  Identification of a Persulfide Group in the Rhodanese-like Domain of MOCS3 by Mass Spectrometry

Abstract: The human MOCS3 protein contains an N-terminal domain similar to the Escherichia coli MoeB protein and a C-terminal segment displaying similarities to the sulfurtransferase rhodanese. MOCS3 is proposed to catalyze both the adenylation and the subsequent generation of a thiocarboxylate group at the C-terminus of the smaller subunit of molybdopterin (MPT) synthase during Moco biosynthesis in humans. Recent studies have shown that the MOCS3 rhodanese-like domain (MOCS3-RLD) catalyzes the transfer of sulfur from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 23 publications
1
63
0
Order By: Relevance
“…Because the proteins for the second step of Moco biosynthesis, MOCS2A, MOCS2B, and MOCS3 are located in the cytosol (14), this would imply a novel function for cytosolic Nfs1 in humans. Human MOCS3 contains a C-terminal rhodanese-like domain which was shown to act as direct sulfur donor for the formation of the thiocarboxylate group on human MOCS2A (13,14). However, the low activity of MOCS3 with thiosulfate and detailed mutagenesis studies of the rhodanese active site loop suggested that thiosulfate is not the physiological sulfur source of MOCS3, and that proteins like L-cysteine desulfurases might perform this function in humans (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the proteins for the second step of Moco biosynthesis, MOCS2A, MOCS2B, and MOCS3 are located in the cytosol (14), this would imply a novel function for cytosolic Nfs1 in humans. Human MOCS3 contains a C-terminal rhodanese-like domain which was shown to act as direct sulfur donor for the formation of the thiocarboxylate group on human MOCS2A (13,14). However, the low activity of MOCS3 with thiosulfate and detailed mutagenesis studies of the rhodanese active site loop suggested that thiosulfate is not the physiological sulfur source of MOCS3, and that proteins like L-cysteine desulfurases might perform this function in humans (12).…”
Section: Discussionmentioning
confidence: 99%
“…After incubation for 12 h at 4°C, L-cysteine was removed by gel filtration. In addition, the MOCS3-RLD-C412A variant was used as a control, to verify the persulfide formation on Cys412 of MOCS3-RLD, which was not detected in this mutant (13).…”
Section: Electrospray Ionization Mass Spectrometry (Esi-ms)-for the Ementioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, the sulfur transfer reaction in higher organisms appears to involve different protein components, as the eukaryotic genes cannot complement their bacterial counterparts. MPT synthase sulfurase is a two-domain protein consisting of an N-terminal adenylation domain (homologous to E. coli MoeB) and a C-terminal rhodanese-like domain (RLD), where the sulfur is bound to a conserved cysteine in the form of a persulfide (38,44). In analogy to the bacterial mechanism, this enzyme is supposed to activate the small subunit of MPT synthase by adenylation followed by sulfur transfer (coming from the RLD), thus forming the thiocarboxylate at the C terminus of the small subunit (2).…”
Section: Biosynthesis Step 2: Synthesis Of Molybdopterinmentioning
confidence: 99%
“…Maximal MPT production was obtained for assays consisting of MOCS3, MOCS2A, and MoaE with sodium sulfide as direct sulfur source or sodium thiosulfate as substrate for MOCS3 (27,43). The fluorescence intensity for the produced Form A in these assay mixtures was set to 100%, and all further assay mixtures were related to this value.…”
Section: Analysis Of the L-cysteine Desulfurase Activity Of Nfs1 In Tmentioning
confidence: 99%